Makna Female Masculinity dalam Kostum Wayang Srikandi Red Batik Solo - Farah Nur Azizah; Yudha Wirawanda (Jurnal Komunikasi, 2019)
This research is a study about the meaning of female masculinity in fashion. The object of analysis is the Javanese figure, Dewi Srikandi in the Red Batik Solo Costume Carnival. This Javanese figure, Dewi Srikandi is interesting to study because she has strong myths about masculinity. Beside that, the researcher also interested in how this female warrior figure looks masculine which is observed from the costumes and accessories worn. The purpose of this study is to find out how does Dewi Srikandi gives the meaning by the costume into the visual of the Red Batik Solo carnival. The analysis uses semiotics Roland Barthes with a qualitative approach and the theory of Female Masculinity Halberstam. The analysis shows that Srikandi is a female character or role that has masculine characteristics that can be observed from analysis of the color, meaning  of denotation and connotation and also meaning of myth, such as red, black, white, brown and dark colors. Masculine also can be shown from Srikandi costumes which are related with syntagmatic and paradigmatic, such as red can be replaced with dark colors (black or brown). In addition, costume accessories such as ricikan (crown, sumping, necklace, bracelet, belt or belt, arrow, and shoes) also give masculine meaning which are indicated by the characteristics of masculine generally, for example strength, courage, aggressiveness, leadership, assertiveness, domination, and violence. Penelitian ini menganalisis mengenai makna Female Masculinity. Objek penelitian ini pada kostum wayang Srikandi yang dibuat oleh Red Batik Solo. Tokoh wayang Jawa Dewi Srikandi ini menarik untuk diteliti karena mempunyai mitos yang kuat tentang karakter wanita yang memiliki sisi maskulin. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana makna yang disampaikan Dewi Srikandi kedalam bentuk visual fashion kostum karnaval Red Batik Solo. Analisis yang digunakan adalah analisis semiotika oleh Roland Barthes dengan pendekatan kualitatif dan teori Female Masculinity Halberstam. Selain itu, peneliti juga tertarik tentang bagaimana tokoh prajurit wanita ini terlihat maskulin yang diamati dari kostum dan aksesoris yang dikenakan. Hasil analisis menunjukkan bahwa Srikandi adalah tokoh puteri yang memiliki sifat maskulin yang dapat diamati dari analisis warna, makna denotasi dan konotasi serta makna mitos, seperti warna merah, hitam, putih, coklat dan warna gelap. Sifat maskulin juga dapat ditunjukkan dari kostum Srikandi yang dihubungkan dengan sintagmatik dan paradigmatik, seperti warna merah dapat diganti dengan warna gelap (hitam atau coklat). Selain itu, aksesoris kostum seperti ricikan (mahkota, sumping, kalung, gelang, ikat pinggang atau sabuk, panah, dan sepatu) juga memberi makna maskulin yang ditunjukkan dari karakteristik yang umumnya dianggap maskulin, misalnya menunjukkan kekuatan, keberanian, agresivitas, kepemimpinan, ketegasan, dominasi, dan kekerasan.